Sports injury rehabilitation: Michelin Star or too many cooks? - Hazlett, A. (Sport Performance & Science Reports, 2021)
When you know how to think, it empowers you well beyond those who know only what to think. Most sporting organisations have historically been a very clinically lead approach to rehabilitation. All medically based practitioners will habitually adopt a clinical reasoning approach to all aspects of their day to day working. However, with the number of non-medical practitioners involved in the process multiplying regularly, it is important to move away from a purely medical model of reasoning and move towards a philosophical approach to working and thinking.